Influence of an intervention program promoting voluntary fasting practices and its perceived barriers among overweight or obese Muslim women working in the public sector, Malaysia - Ismail, Suriani; Abdul Manaf, Rosliza; Mahmud, Aidalina; Shamsuddin, Khadijah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: This article aims to describe the effect of an intervention to promote the practice of voluntary Islamic fasting and its barriers among a group of overweight and obese Muslim women working in the public sector in Malaysia. Materials and methods: In this quasi-experimental study, an intervention to encourage voluntary fasting was delivered in a half day seminar, supported by relevant booklets prepared. A self-administered questionnaire was used to capture data on voluntary fasting practices and its perceived barriers before and four months after the intervention. Data was analysed using Mc Nemar test to compare the proportion before and after the intervention. Significant level was set at p<0.05. Results: A total of 56 women were recruited. Their mean age was 36.65 years, most were married, had formal education up to secondary level and median income of RM 3000 per month. At baseline, 60.7% of them have practiced voluntary fasting. After intervention, the number of participants who practices voluntary fasting increased with a significant increase in three types of voluntary fasting (i.e. Mondays only, Thursdays only and 6 days in Shawal). The highest barrier to practice voluntary fasting was having no motivation to do so, followed by work commitment, health problems and family commitment. Discussion and Conclusion: Most of the respondents could practice voluntary fasting regularly if motivated to do so and backed by social support both at work and at home.